Lrig1 is a cell‐intrinsic modulator of hippocampal dendrite complexity and BDNF signaling - Alsina, Fernando Cruz (EMBO Rep, 2016)
Even though many extracellular factors have been identified as promoters of general dendritic growth and branching, little is known about the cell‐intrinsic modulators that allow neurons to sculpt distinctive patterns of dendrite arborization. Here, we identify Lrig1, a nervous system‐enriched LRR protein, as a key physiological regulator of dendrite complexity of hippocampal pyramidal neurons. Lrig1‐deficient mice display morphological changes in proximal dendrite arborization and defects in social interaction. Specifically, knockdown of Lrig1 enhances both primary dendrite formation and proximal dendritic branching of hippocampal neurons, two phenotypes that resemble the effect of BDNF on these neurons. In addition, we show that Lrig1 physically interacts with TrkB and attenuates BDNF signaling. Gain and loss of function assays indicate that Lrig1 restricts BDNF‐induced dendrite morphology. Together, our findings reveal a novel and essential role of Lrig1 in regulating morphogenic events that shape the hippocampal circuits and establish that the assembly of TrkB with Lrig1 represents a key mechanism for understanding how specific neuronal populations expand the repertoire of responses to BDNF during brain development.